Recruitment Analysis in Small and Medium Scale Construction Companies - T S, Mukesh; K, Sampathkumar; P, Kulanthaivel (International Journal of Scientific Research in Civil Engineering, 2016)
Human resource management practices are widely analysed for the employee concerns and for the company's progress in the advancing state. This project work is done to carry out a study of the Indian construction sector's recruitment process. In particular, emphasis has been made on the small and medium size organisations as there is a lack of good and sound HRM practises, our research will furnish a model which will help enhance the hiring process in companies at the small and medium size levels. This study is purely based on competency approaches in recruitment. Extensive literature review and face to face interactions with company officials at the initial stage helped us realise the important competencies that are relevant to the construction sector, in particular, to the role of site engineer. A questionnaire was created further and was floated out to different companies falling under the specified category (Small and Medium scale). Later SPSS and Microsoft Excel were used to analyse the responses Based on the results obtained, a competency based model was developed that will ultimately help in enhancing the recruitment process of site engineers in small and medium size construction companies.
Keywords: Competency; Contextual; Recruitment; SPSS